Bach's Operas of the Soul: A Listener's Guide to the Sacred Cantatas - Ringer, Mark (Amadeus Press, 2021)
Bach’s Operas of the Soul is the first introduction to Bach’s sacred cantatas for the general music lover.In clear and accessible language, Mark Ringer examines this vast output of masterpieces as the great musical dramatic creations that they. Bach’s sacred cantatas represent an almost superhuman artistic and spiritual achievement, arguably the richest investment by a great composer within a single genre. But outside of a handful of pieces, they remain a closed book to a majority of serious listeners already familiar with Bach’s large-scale religious works. Nevertheless, the same musical-dramatic genius of Bach’s Passions is fully evident in virtually all of the composer's sacred cantatas. Ringer approaches the sacred cantatas as sermons in musical-dramatic form, un-staged operas, planned for each occasion of the church year. Bach’s era relished dramatic contrast, and his use of the human voice offers a constantly changing pallet of vocal colors. The singers play ‘roles’ throughout the cantatas from penitent sinner, to ardent believer, to Christ himself.This book is accompanied by online audio tracks of select Bach canatatas from the Naxos music library. It will be of use to readers interested in opera and vocal music who have already come to love Bach’s Passions and who want to familiarize themselves with this wide array of masterpieces.